Microwave‐Assisted Decarbonylation of Biomass‐Derived Aldehydes using Pd‐Doped Hydrotalcites. Issue 2 (30th October 2019) - An, Nan; Ainembabazi, Diana; Reid, Christopher; Samudrala, Kavya; Wilson, Karen; Lee, Adam F.; Voutchkova‐Kostal, Adelina
Abstract: Catalytic decarbonylation is an underexplored strategy for deoxygenation of biomass‐derived aldehydes owing to a lack of low‐cost and robust heterogeneous catalysts that can operate in benign solvents. A family of Pd‐functionalized hydrotalcites (Pd‐HTs) were synthesized, characterized, and applied to the decarbonylation of furfural, 5‐hydroxymethylfurfural (HMF), and aromatic and aliphatic aldehydes under microwave conditions. This catalytic system delivered enhanced decarbonylation yields and turnover frequencies, even at a low Pd loading (0.5 mol %). Furfural decarbonylation was optimized in a benign solvent (ethanol) compatible with biomass processing; HMF selectively afforded an excellent yield (93 %) of furfuryl alcohol without humin formation; however, a longer reaction favored the formation of furan through tandem alcohol dehydrogenation and decarbonylation. Yields of the substituted benzaldehydes (37–99 %) were proportional to the calculated Mulliken charge of the carbonyl carbon. Activity and selectivity reflected loading‐dependent Pd speciation. Continuous‐flow testing of the best Pd‐HT catalyst delivered good stability over 16 h on stream, with near‐quantitative conversion of HMF. Abstract : Pd‐functionalized hydrotalcites (Pd‐HTs) are used for the decarbonylation of furfural, 5‐hydroxymethylfurfural, and aromatic and aliphatic aldehydes under microwave conditions. The catalytic system delivers enhanced decarbonylation yields and turnover frequencies, even at a low Pd loading (0.5 mol %).